Corticostriatal glutamate‐mediated dynamic therapeutic efficacy of electroacupuncture in a parkinsonian rat model - Xinxin Jiang; Min Sun; Yitong Yan; Yanhua Wang; Xinyu Fan; Jing Wei; Ke Wang; Peirong Liang; Zirui Wang; Jihan Wang; Xiaomin Wang; Jun Jia (Clinical and Translational Medicine)
Abstract Background Motor impairments are the defining cardinal features of Parkinson's disease (PD), resulting from malfunction of the cortico‐basal ganglia circuit. Clinical data have demonstrated that electroacupuncture (EA) stimulation may benefit motor symptoms in PD without adverse effects. However, the specific effects of EA on PD and the underlying mechanisms remain largely unclear. Methods This study investigated the effects of EA stimulation during and after 100 Hz application in a rat model of PD created by unilateral injection of 6‐hydroxydopamine (6‐OHDA). To establish optimal treatment parameters of EA, motor behaviours were dynamically assessed using open field and rotarod tests. Additionally, we evaluated corticostriatal spine plasticity using immunoelectron microscopy and measured the levels of dopaminergic and glutamatergic neurotransmitters through microdialysis, in vivo electrochemistry and high‐performance liquid chromatography. Neural activity dynamics were recorded by measuring local field potentials in both the motor cortex and the striatum. Furthermore, chemogenetic techniques were employed to manipulate corticostriatal glutamatergic neurons and clarify the mechanisms that contribute to the therapeutic benefits of EA in the PD rat model. Results Chronic EA stimulation resulted in a gradual and long‐lasting alleviation of motor symptoms, independent of nigrostriatal dopamine (DA) restoration. Notably, EA stimulation modulated corticostriatal spine plasticity and reduced excessive glutamate transmission in PD model rats. Moreover, EA effectively inhibited aberrant corticostriatal synchronised high‐beta (25–40 Hz) oscillations, which serves as a pathological biomarker of PD. Conversely, chronic chemogenetic activation of corticostriatal glutamatergic neurons hindered these positive outcomes of EA treatment in PD model rats. Conclusions This study sheds light on the temporal dynamics and optimal parameters of EA treatment in PD. It emphasises the significance of inhibiting corticostriatal glutamate transmission in EA's therapeutic benefits for PD. Targeting glutamatergic neurons with EA holds promise as a non‐dopaminergic intervention for managing motor symptoms and abnormal neural activity with PD. Key points EA commonly protects dopaminergic neuronsby reducing neuroinflammation, oxidative stress, and apoptosis. New findings reveal that EA alleviates motor symptoms in a parkinsonian rat model without restoring striatal dopamine levels. EA effectively suppresses excessiveglutamate transmission and high‐beta synchronization, contributing to motorsymptom relief. Activation of corticostriatalglutamatergic projections may hinder the efficacy of EA.